Bilateral Intraoral Mucosal Flaps for Repair of Vestibular Stenosis Following Rhinoplasty & Airway Reconstruction: A Case Report - Brian P Dickinson; Monica Vu; Nikkie Vu-Huynh (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Background: Aesthetic rhinoplasty is a challenging specialty for surgeons as both the demands​ of patients and physicians are high. Preservation rhinoplasty brings many advances and advantages to the rhinoplasty with the intent of decreasing the need for revision or secondary rhinoplasty through change that is less destructive. Nonetheless, there are often patients in the rhinoplasty surgeon's practice who have either aesthetic or functional sequelae from previous open or more reduction-oriented procedures. One of the more troublesome complications for the patient to live with, and the surgeon to correct, is vestibular stenosis.  Purpose: To present a simple method and technique for repairing vestibular stenosis that is​ easily reproducible. We present a technique previously described for repair of cleft-lip and palate rhinoplasty sequelae, but not frequently utilized in the aesthetic rhinoplasty population. This technique is within the same operative field and does not require additional cartilage grafts.  Method/Results: A 25 year old female Middle Eastern patient underwent septorhinoplasty to​ reduce the size of her nose and improve breathing. The patient underwent a revision operation to further reduce her nose and with the addition of nostril sill excisions. The patient did well post-operatively, but eventually developed difficulty breathing and bilateral circumferential webs of the nasal vestibule. This was corrected with bilateral, medially-based 1.5cm width and 3cm length intraoral mucosal flaps to the nostril sill and the floor of the nasal airway. The flaps were inset with 4.0 chromic suture, and the intraoral harvest site was closed with chromic suture. The nose was then stented with Doyle splints bilaterally. The patient started hyperbaric oxygen therapy 1 day post-operatively and received 5 consecutive treatments in total.  Conclusion: From a functional and aesthetic standpoint, cicatricial vestibular stenosis following​ aesthetic rhinoplasty is a challenging problem to correct. The intraoral mucosal flap offers a viable option which is easily reproducible and is within the same operative field. Hyperbaric oxygen therapy is a useful adjunct for flap viability.